In-bore MRI-guided prostate biopsy in a patient group with PI-RADS 4 and 5 targets: A single center experience. Issue 141 (August 2021) - Vural, Metin; Coskun, Bilgen; Kilic, Mert; Durmaz, Selahattin; Gumus, Terman; Cengiz, Duygu; Onay, Aslihan; Saglican, Yesim; Colakoglu, Bulent; Akpek, Sergin; Yildirim, Hakan; Esen, Tarik; et al.
Highlights: In- bore prostate biopsy has a high detection rate of csPCa in patients with high likelihood PI-RADS scores. Higher suspicion of mpMRI resulted in higher overall PCa and csPCa. The first two biopsy cores were sufficient to diagnose csPCa and reach concordance with RP GS. Abstract: Purpose: To determine the diagnostic yield of magnetic resonance imaging (MRI) guided in-bore biopsy in patients with high likelihood multiparametric MRI (mpMRI) findings, regarding overall and clinically significant prostate cancer (csPCa) detection rates and concordance of biopsy and radical prostatectomy (RP) Gleason scores (GS). Methods: This retrospective study consisted of 277 Prostate Imaging Reporting and Data System (PI-RADS) assessment category 4 and 5 targets in 246 patients (mean age, 65.7 years; median prostate specific antigen value, 7.75 ng/mL) who had undergone in-bore biopsy at our institution between 2012 and 2020. Eighty-one patients who underwent RP were eligible for the concordance analysis of biopsy and RP specimen GS. Results: Overall PCa detection rates were 80.5 % per patient (198/246) and 78 % per target (216/277) and 83.5 % and 67.4 % in primary (biopsy naive) and secondary (at least one negative prior biopsy) settings. csPCa was found in 63 % overall, 66 % of patients (132/200) in the primary, and 50 % of patients (23/46) in the secondary biopsy settings (p < 0.001). The prostate cancer detection rate was 68 % and 92 % in PI-RADS 4 and 5, respectively (p < 0.001). In the radical prostatectomy subcohort, 27.2 % of patients were upgraded, 8.6 % of patients were downgraded from needle biopsy. Significant complications occurred in 1.2 % of patients. Conclusions: MRI-guided in-bore prostate biopsy has a high detection rate of csPCa in primary and secondary biopsy cohorts. Biopsy results were satisfactory in terms of the number of positive cores, cancer percentage in positive cores, and concordance of GS in needle biopsy and RP specimen.